Analisis Penggunaan Google Meet dalam Pembelajaran terhadap Kecerdasan Emosional Siswa - Ema Fidiatun Khasanah; Devi Erlistiana; Unik Hanifah Salsabila; Elitawati (Jurnal Tinta: Jurnal Ilmu Keguruan dan Pendidikan, 2022)
In the current era of online learning since the Corona pandemic, many platforms are used to simplify the learning process. Like the Google Meet platform, one of the applications used. Students' emotional intelligence will be influenced by what tools are used in learning. The usefulness of this application can be accessed easily anytime and anywhere, and the advantages of this application include making it easier to communicate so that interaction can occur even though they are in different places and one of the drawbacks is that if it is used for a large number of participants there is a provision to pay and can’ot change the background at will. The method is carried out by sampling a questionnaire that was carried out at SMA Muhammadiyah 1 Banjarnegara in class 12 and received 66 responses. By using this method, the results of the data in the form of emotional intelligence can be influenced by the platform because in the learning there is still interaction between teachers and students as well as students with students even though they are separated by different distances and spaces so that students can receive and understand the material presented by the teacher when learning takes place using Google Meet because this platform can display presentations or powerpoints so that it can facilitate the learning process.